Konstruksi Kepemimpinan Dalam Rumah Tangga Istri Pencari Nafkah Utama Dalam Bingkai Hukum Islam dan Hukum Positif di Kota Bengkulu - Zurifah Nurdin (Manhaj: Jurnal Penelitian dan Pengabdian Masyarakat, 2019)
This research was motivated by the husband's unpreparedness and unwillingness to fulfill a living for his wife and children, even though the responsibility of living is assumed by him. The wife was used as an ATM  for the husband so that he becomes a colonized creature both physically and mentally. Islamic law and positive law uphold benefits in order to achieve justice, therefore positioning the wife as the main breadwinner and leader even head of the family is legitimate based on the theory of maslahah al mursalah and maqashid asyari'ah. The husband will be positioned as a leader if he fulfills a living for his wife and children, both inner and outer.